Body size correlations with female aggression and physiology suggest pre-adult effects on caste in an independent-founding eusocial paper wasp (Mischocyttarus pallidipectus, Hymenoptera Vespidae). Issue 2 (4th March 2023) - Fiocca, Katherine; Congdon, Rheanna; O'Donnell, Sean
Abstract : Reproductive castes are a defining characteristic of eusocial insects. The developmental timing of reproductive caste differentiation is important to shaping individual opportunities for reproductive flexibility. Because hard-part body size (e.g., wing length) is fixed for insects upon adult emergence, morphology can be used to assess pre-adult effects on caste status. Differences in body size amongst adult colony mates may affect social competition for resources and reproductive status in caste-monomorphic species. Our goal was to use body size correlations with female behavior and physiology to test among three hypotheses for pre-emergent effects on female caste within colonies of Mischocyttarus pallidipectus paper wasps: (1) no size overlap between females with developed and undeveloped ovaries would indicate caste is likely determined during larval development; (2) size bias for reproductives with exceptions: caste could be biased during development, but post-emergence factors may play a role; (3) no size patterns: no morphological evidence for pre-adult caste biases. Within colonies, we found a significant difference in body size (wing length) between females with developed vs undeveloped ovaries: larger females were more likely to have developed ovaries. Additionally, larger females were more aggressive towards nestmates. However, there was considerable variation in body size effects on both ovary development and behavioral dominance: even some of the smallest-bodied females had developed ovaries and were socially aggressive. These data suggest factors during pre-adult development lead to morphological (size) differences, and that body size affects the outcome of adult interactions with implications for reproductive caste.